Nefroctomia 5/6 e sua influência na permeabilidade colônica de água e eletrólitos em ratos acordados. - Freire, Elionai Gomes (2016)
The nephrectomy 5/6 is a surgical procedure most commonly used in physiology laboratories to reproduce chronic renal failure due to its reproducibility and practicality. Patients with IR or nephrectomized present hemodynamic disorders such as fluid overload and accumulation of azotônicas substances in plasma, which can have serious complications in various organs. The aim of this research was to evaluate the changes that nephrectomy 5/6 can cause colonic permeability of rats to water and electrolytes (Na+,K+,Cl-) after 3,7 and 14 days of renal failure The project was approved by CEUA-UFC protocol with n° 11/15. 92 animals were used (male rats Wistar, weighing 280- 300 g) divided into three groups 3 days post-nephrectomy 5/6 7-days nephrectomy 5/6 and 14 days after nephrectomy 5 / 6- each group being formed by a SHAM and an experimental. For studies of colonic permeability of water and electrolytes, the animals were anesthetized with urethane, and then subjected to colonic infusion Tyroad + phenol red for 60 min. For all experiments, we monitor hemodynamic parameters (systolic-PAS blood pressure, central venous pressure, PVC, often heart-FC and blood volume- VS) and also biochemical plasma concentrations of urea and creatinine. Our biochemical results of bun and serum creatinine in groups 7 and 14 days confirmed the renal failure after nephrectomy 5/6 (114,8±1,8dl/ml; 165,6±7,2dl/ml) e (0,95±0,02dl/ml; 1,3± 0,07dl/ml) respectively. Groups 7 and 14 days post-nephrectomy 5/6 also showed significant blood volume changes (11,12±0,37 ml) e (15,83±0,82ml) The group 3 days did not present biochemical or significant hemodynamic results and insignificant colonic secretion of water and electrolytes (Na+,K+,Cl-) Correlation by linear regression curves between the colonic secretion of water and electrolytes in the blood volume in the group 7days performed quite significant in this work. We conclude that the 5/6 nephrectomy proved effective in chronic renal failure model, as promoted successive rise in urea levels and serum creatinine. The nephrectomy 5/6 promoted colonic secretion into water and electrolytes becoming evident in rats in groups 7 and 14 days post-nephrectomy. The close relationship of blood volume changes in group 7 days with the secretion of water and electrolytes (Na+, k+, Cl-) It makes us deduct be plasma hyperglycemia induced by 5/6 nephrectomy the decisive for absorption and secretion of these ions or in the colon.